INTRODUKSI TEKNOLOGI BUDIDAYA DAN PENGOLAHAN PRODUK LEBAH GALO-GALO SEBAGAI SUPLEMEN PENCEGAHAN STUNTING DI NAGARI BUKIK SIKUMPA KABUPATEN LIMA PULUH KOTA - Zulkarnaini Zulkarnaini; M Teguh Imam Wijaya; Suci Rahmadani (LPPM Universitas Andalas, 2023)
Honey has long been recognized for its beneficial properties for human health. Galo-galo honey is proven to contain various beneficial substances for human health, including minerals, polyphenols, vitamins, amino acids, carotenoids, enzymes, organic acids, and volatile compounds. However, many people still doubt the authenticity of honey available in the market. This activity aims to socialize the potential of galo-galo beekeeping and the benefits of galo-galo honey in supporting community health, as well as a nutritious food source for toddlers experiencing stunting. The cultivation of galo-galo bees is expected to become an additional source of income for the residents of Nagari Bukik Sikumpa, Lareh Sago Halaban District. This activity involves direct socialization and training for the community by galo-galo beekeepers, including visits to galo-galo bee houses. The outcome of this activity shows the high enthusiasm of the community toward this initiative, with active participation and numerous inquiries about the techniques of cultivating galo-galo bees and their benefits. Through this outreach program, the community's knowledge about the benefits and advantages of galo-galo bees has increased. This knowledge is not only beneficial in the context of galo-galo honey cultivation and production as a sideline business but also has a positive impact on overall community health. Specifically, galo-galo honey can be used as an additional nutritional source to assist toddlers experiencing stunting in Nagari Bukik Sikumpa. Thus, this activity holds significant potential to improve community welfare and support efforts to enhance the health of children in that community.